Kongens Falds positionering på tværs af markeder: Den danske og den tysksprogede modtagelse i boghistorisk lys - Wenusch, Monica (Passage - Tidsskrift for litteratur og kritik, 2022)
In my article I examine the diverging and manifold images of the novel Kongens Fald as depicted in resp. the Danish and German-speaking contemporary reception, due to the different conditions and contextualizations in the resp. book markets. Theoretically my analysis is mainly based on D.F. McKenzie’s thoughts outlined in “The Book as an Expressive Form” (1985).